Implementation of 21st Century Learning through The Stages of Teaching at The Right Level Approach for Students of Integrated Islamic Elementary Schools - Muhajang, Tatang; Suryanti, Yanti (Pedagonal : Jurnal Ilmiah Pendidikan, 2024)
21st-century skills generally refer to the core competencies of digital learning, critical thinking, and real-world problem-solving. These skills are developed to help learners cope with modern developments. Learners are seen as individuals who are active learners, rather than spectators and listeners. The study aimed to investigate the implementation of 21st-century learning through the application of the Teaching at the Right Level (TaRL) approach.  The research method is descriptive qualitative, which describes the results of interviews, questionnaires, and observations conducted by researchers. The results of the data analysis of fourth grade students in IPAS (Social and Science Subject) learning show better results, the mean score of students is 82.21 with the performance of students above the criteria for achieving learning goals as high as 84 percent, i.e. 16 students and 16 percent, i.e. 3 students have still not achieved KKTP. The highest score is 100 and the lowest score is 41. The percentage shows that the implementation of 21st-century learning by applying the TaRL approach helps students develop critical thinking, problem-solving, and intellectual skills and shows that students' learning outcomes have improved.